Computing Three-Dimensional Freeform Reflectors with a Scattering Surface - Kronberg Vì C.E.; Anthonissen Martijn J.H.; ten Thije Boonkkamp Jan H.M.; IJzerman Wilbert L. (EPJ Web of Conferences, 2023)
We present a novel approach to computing reflectors with a scattering surface in illumination optics. A scattering model governed by a Fredholm integral equation is derived. Solving this integral relation yields a virtual specular target distribution, which we insert into a Monge-Ampère least-squares numerical solver to get a scattering reflector that yields the desired illumination.